LEGAL POLITICS AND POWER DOMINANCE IN THE FORMATION OF NATIONAL STRATEGIC REGULATIONS: THE CRISIS OF CHECKS AND BALANCES IN INDONESIAN DEMOCRACY - Iskandar Syukur (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2024)
The formation of national strategic regulations in Indonesia demonstrates increasing attention to the relationship between legal politics and the use of power in the process of state governance. Regulations that play a crucial role in supporting the national agenda are often influenced not only by development needs and government interests but also by the power relations that develop in the decision-making process. This situation raises concerns about the implementation of checks and balances mechanisms, particularly when the policy-making process shows a tendency towards a concentration of influence among certain actors within the government system. This study aims to analyze the influence of legal politics and the dominance of power in the formation of national strategic regulations and their implications for the implementation of checks and balances in Indonesia's democratic system. This study uses a qualitative approach with a literature study method through the utilization of various relevant sources, such as scientific articles, previous research results, books, and various documents related to the research focus. The results show that the direction of legal politics in the formation of national strategic regulations is closely related to various state interests and policy orientations that develop in governance. The dominance of power in the legislative process has been shown to influence the effectiveness of the oversight function between state institutions, the balance of authority, and institutional independence in the implementation of the control function over policy. This situation has implications for the quality of Indonesian democracy through its influence on public participation, public trust, representation, and accountability in state administration.